2007
DOI: 10.1111/j.1574-6968.2006.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the zinc metalloprotease EmpA ofVibrio anguillarum

Abstract: The extracellular zinc metalloprotease, EmpA, is a putative virulence factor involved in pathogenicity of the fish pathogen Vibrio anguillarum. The 611-amino acid precursor of this enzyme is encoded by the empA gene. The residues His346, His350, Glu370, Glu347, His429, Tyr361 and Asp417 are highly conserved and putatively function together at the active site of the enzyme. In this study, empA was inserted into pET24d(+) and expressed in Escherichia coli strain BL21(DE3) as a 6 x His tagged protein (r-EmpA). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The 36-kDa peptide was detected only if protein samples were boiled prior to SDS-PAGE and Western blot analysis (29)(30)(31). Similar results were obtained using V. anguillarum W-1 supernatant (31).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The 36-kDa peptide was detected only if protein samples were boiled prior to SDS-PAGE and Western blot analysis (29)(30)(31). Similar results were obtained using V. anguillarum W-1 supernatant (31).…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies using recombinant EmpA synthesized in E. coli (29)(30)(31) have suggested that the presence of a stable ϳ36-kDa EmpA form is the result of a thermoinduced self-proteolysis of a 44.6-kDa precursor (30). The 36-kDa peptide was detected only if protein samples were boiled prior to SDS-PAGE and Western blot analysis (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular proteolytic activity in cell-free supernatants was determined by azocasein assay (Secades et al, 2001) proteolytic enzymes, as reported in Vibrio cholerae, in which production is increased in hyperswarmer mutants (Gardel & Mekalanos, 1996). Extracellular proteolytic activities have been reported to be involved in the virulence of different pathogens, including a number of fish pathogenic bacteria (Fernández et al, 2003;Yang et al, 2007;Zhang et al, 2009). However, the implication of proteases in pathogenesis is not a general rule, as shown in this study in a rainbow trout model.…”
Section: Discussionmentioning
confidence: 59%
“…Although extracellular proteolytic enzymes have been considered as virulence factors in many bacterial fish pathogens, comparative analyses of wild-type strains and isogenic mutants devoid of proteolytic activity have seldom been performed. In particular, proteases from Vibrio anguillarum (Yang et al, 2007), Yersinia ruckeri (Fernández et al, 2003), Pseudomonas fluorescens (Zhang et al, 2009) and Moritella viscosa (Bjornsdottir et al, 2009) have been clearly proved to be involved in bacterial virulence in fish.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with wild type strain, this mutant had a 1,000-fold higher LD 50 value after immersion infection of rainbow trout. In the work of Yang et al (2007), it is also proposed that an extracellular zinc metalloprotease, EmpA, is a putative virulence factor of the fish pathogen L. anguillarum.…”
Section: Extracellular Proteasesmentioning
confidence: 99%